Single family housing estates of the post-war era - A European comparison of opportunities and risks - 5th September 2013. Workshop. Documentation. - (:unkn) unknown (My University, 2014)
Die Beiträge im Einzelnen: Andrea Berndgen-Kaiser: The future of mature housing estates in Germany - Recommendations for municipalities to support the longterm sustainable use of houses built from the 1950s to the 1970s (S. 8 ff.); Huibert A Haccoû, Stefan Netsch: Emerging trends and their demographic origins; their impact on the US, EU and Dutch housing markets (S. 24 ff.); Ute Cornec: A strategy for dealing with older housing estates built in the 1960s and 1970s in Havixbeck (Münsterland) (S. 34 ff.); Anne-Françoise Marique, Jean-Marie Halleux: Renewal of Walloon suburban neighbourhoods and perspectives for a research project on "suburban densification" (S. 43 ff.); Yves Jouffe, Leslie Belton-Chevallier: A "triple bind ": local attitudes to the energy crisis. A theoretical discussion on the situation of low-income households in French periurban neighbourhoods (S. 54 ff.); Michel Rousset : Build In My Back Yard experiments (BIMBY) - from noticing the benefits for everyone to a negotiated urban planning. Redensification of detached housing areas in the Eure Department (Upper Normandie), a negotiated utopia? (S. 68 ff.).
Keywords: Stadtentwicklung; Stadtentwicklungsplanung; Wohnungsbestand; Einfamilienhaus; Bewohnerbefragung; Umbau; Siedlungsstruktur; Stadtumland; Stadtrand; Beispielsammlung; Einfamilienhaussiedlung; Sechziger Jahre; Siebziger Jahre; Stadtumbau; Weiternutzung; Peripherie; Nachverdichtung; Niedrigeinkommen